2018
DOI: 10.1177/2325967118816300
|View full text |Cite
|
Sign up to set email alerts
|

Injury Surveillance and Evaluation of Medical Services Utilized During the 2016 Track and Field Olympic Trials

Abstract: Background:Injury surveillance systems have been implemented at world championships, yet no previous work has determined the burden of injuries during the United States Track and Field Olympic Trials. Additionally, the type of medical service providers utilized throughout the meet has not been reported, leaving it unclear whether optimal staffing needs are being met.Purpose:To describe the incidence of injuries presenting to the medical team at the 2016 US Track and Field Olympic Trials (Eugene, Oregon) by eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…The most common injury locations in the current study were the posterior thigh and lateral ankle, which is consistent with previous studies. 1,9 The characteristics of each track and field event are evident from the commonly reported injuries for that event. Long jump, triple jump, and pole vault involve maximum sprinting in the run-up and explosive power in a short duration of time at takeoff, suggesting that the hamstring is heavily loaded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common injury locations in the current study were the posterior thigh and lateral ankle, which is consistent with previous studies. 1,9 The characteristics of each track and field event are evident from the commonly reported injuries for that event. Long jump, triple jump, and pole vault involve maximum sprinting in the run-up and explosive power in a short duration of time at takeoff, suggesting that the hamstring is heavily loaded.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have reported on track and field injuries that occurred during competition. 1,7,8 Observational studies have focused on specific body locations or injury types. 5,6,11 Only a small number of comprehensive surveys have been reported on time loss due to injuries.…”
mentioning
confidence: 99%
“…In the event of acute infections, both officials and athletes can spread and be at risk of becoming infected. Yet the prevalence of injury and illness among officials is limited 5 . Information on the type of medical services needed and utilised, is essential for the contingent medical team planning especially in resources management of medical supplies, medications, and medical staff 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Chiropractors are frequently classified as CAM service providers and claim a role as service providers in elite level athletic health and performance [ 9 , 10 ]. Generally speaking, their inclusion is attributed to the needs expressed by athletes or other influential individuals, rather than a clear appreciation of the full spectrum of the chiropractor’s clinical skillset.…”
Section: Introductionmentioning
confidence: 99%